Understanding adult learners’ motivation and preferences in online and distance programs in the post COVID-19 era: a case study of the Institute of Continuing Education & Professional Studies / Mazlifah Mansoor ... [et al.] - Mansoor, Mazlifah; Dahalan, Noor Azura; Abdul Azis, Maz Ainy; Abdul Rahim, Ramita; Temyati, Zawawi (UiTM Press, 2024)
As online distance learning continues to gain popularity, it becomes increasingly essential to gain insights into the distinctive motivations and preferences of adult learners. These insights are critical for the development of effective and engaging educational programs. This article conducts an examination of the motivations and preferences of adult learners, highlighting how program designers can tailor their approaches to enhance the educational experience. The study adopts a mixed methods research design, drawing upon both quantitative and qualitative data collected from a participant group consisting of 1582 students affiliated with the Institute of Continuing Education & Professional Studies (iCEPS). Among these participants, 72.3% endorse the concept of a fully online distance program (ODL), while 21.4% express a preference for a blended program, and 6.3% express a strong inclination toward exclusively face-to-face learning. When delving into the motivations behind the ODL program, the respondents emphasise certain factors. The most prominent of these is the effectiveness of cost reduction in education, garnering a substantial score of 57.4%. Additionally, 51% of participants prioritize time efficiency, encompassing reduced commute times and the flexibility to utilize various devices for learning. In contrast, the two aspects that receive comparatively lower scores are student satisfaction through ODL (37.6%) and the efficiency of data presentation (35.8%). Qualitative content analysis unearths dissatisfactions within the realm of ODL, attributed to factors such as social isolation, limited adaptability for dynamic interaction, challenges related to technological infrastructure and access, as well as perplexities associated with assessment methods in the ODL context. To address these learning preferences and enhance the overall satisfaction of students engaged in ODL, educational institutions and policymakers are encouraged to contemplate a range of support measures. These measures encompass ensuring equitable access to technology, providing comprehensive academic and student support services, crafting responsive course materials, and fostering a sense of community and engagement among learners.